SIPAKATAU and Inclusive Education: Fostering Social Harmony for Sustainable City Development - Irwan Abbas; Rustam Hasim; Laode Monto Bauto; Peribadi Peribadi; Abur Hamdi Usman (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2025)
This article examines the intersection of SIPAKATAU a Bugis-Makassar cultural philosophy that emphasizes mutual respect, dignity, and social harmony with inclusive education as a strategy for fostering sustainable urban development in Makassar. The objective of this study is to investigate how local wisdom can be integrated into educational frameworks to promote social cohesion in increasingly diverse urban environments. Employing a qualitative methodology, including document analysis and literature review, this research identifies key SIPAKATAU principles that align with inclusive education values, such as justice, empathy, and collaboration. The findings reveal that incorporating these cultural elements into school curricula and policies strengthens community participation, enhances conflict resolution, and supports marginalized groups. These outcomes contribute significantly to building socially resilient and sustainable cities. The study proposes a theoretical framework for policy adaptation that incorporates local cultural values into inclusive education practices, demonstrating that traditional wisdom can play a vital role in addressing contemporary challenges of urban sustainability.